References to women in Plato’s Timaeus: Reading notes about their biological aspect, social function, and metaphoric valence - De Simone, Pia (Revista Archai, 2020)
This work aims to investigate the occurrences of the female lexicon, in particular Î³Ï…Î½Î® and Î¼Î®Ï„Î·Ï, in the Timaeus, to bring out Plato’s position regarding women that can be deduced from the hermeneutics of the examined passages. It is necessary to consider all the problems related to Plato’s writings, including the argumentative structures used and the complexity of some concepts. The occurrences in the Timaeus, although not numerically conspicuous, are significant in terms of content, given the very nature of this dialogue, which aims to identify the position and role of man and his soul in the cosmos. In Timaeus’ Prologue, such as in the Republic, Plato expresses more open positions regarding the social role of women; instead in other passages, such as those dealing with the transmigration of souls, Plato uses images relating to women to help his listeners to understand very complex issues. These images, to be understandable, have to be adequate to the idea about women common to Plato’s time.